2019
DOI: 10.1111/apv.12227
|View full text |Cite
|
Sign up to set email alerts
|

Trading places: Inclusive cities and market vending in the Pacific Islands

Abstract: Rapid population growth in Pacific island cities far exceeds employment opportunities and is contributing to rising urban inequality and social exclusions. Livelihoods in the informal urban sector, such as market vending, provide much needed income, rural-urban connectivity and food security, but remain largely excluded from policy and planning frameworks. Spatial, economic and social exclusions limit vendors' economic advancement, their influence over decision-making, and their access to basic services. Local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Three studies were conducted in the least developed countries, namely Uganda, Bangladesh and Cambodia (Young, 2018;Narula, 2019;Tanaka & Hashiguchi, 2020). Fourteen studies were conducted in developed countries, namely the United States, the United Kingdom, Brazil, South Korea, Lithuania, Russia, Australia and Slovenia (Autrey et al, 2014;Williams & Harodnik, 2015a;Williams & Harodnik, 2015b;Kim & Kim, 2016;Visser, 2017;Abdel-Latif et al, 2017;Milovanova et al, 2018a;Milovanova et al, 2018b;Kireenko & Nevzorova, 2019;Keen & Ride, 2019;Navickas et al, 2019;Fedotov et al, 2020;Bayar et al, 2020). In developing countries, 12 research have been identified to be relevant with effects of the informal economy towards employment, namely Malaysia, Brazil, South Africa, Turkey, Croatia, India, Pakistan, Indonesia and Colombia (Bosch & Pretel, 2015;Tijdens & Besamusca, 2015;Rothenberg et al, 2016;Williams & Franic, 2016;Elveren & Osgur, 2016;Tan et al, 2016;Shembavnekar, 2019;Dominguez, 2019;Ullah et al, 2019;Avenyo et al, 2020;Santoso & Sriyana, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were conducted in the least developed countries, namely Uganda, Bangladesh and Cambodia (Young, 2018;Narula, 2019;Tanaka & Hashiguchi, 2020). Fourteen studies were conducted in developed countries, namely the United States, the United Kingdom, Brazil, South Korea, Lithuania, Russia, Australia and Slovenia (Autrey et al, 2014;Williams & Harodnik, 2015a;Williams & Harodnik, 2015b;Kim & Kim, 2016;Visser, 2017;Abdel-Latif et al, 2017;Milovanova et al, 2018a;Milovanova et al, 2018b;Kireenko & Nevzorova, 2019;Keen & Ride, 2019;Navickas et al, 2019;Fedotov et al, 2020;Bayar et al, 2020). In developing countries, 12 research have been identified to be relevant with effects of the informal economy towards employment, namely Malaysia, Brazil, South Africa, Turkey, Croatia, India, Pakistan, Indonesia and Colombia (Bosch & Pretel, 2015;Tijdens & Besamusca, 2015;Rothenberg et al, 2016;Williams & Franic, 2016;Elveren & Osgur, 2016;Tan et al, 2016;Shembavnekar, 2019;Dominguez, 2019;Ullah et al, 2019;Avenyo et al, 2020;Santoso & Sriyana, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…According to Williams & Harodnik (2015), the informal economy's undeclared jobs support the formal economy's disparities rather than reduce the disparities. Also, the informal economy acts as a solution, especially during tough times (Abdel-Latif et al, 2017;Keen & Ride, 2019). However, with limited access to financial resources and security protection, people's welfare will decline (Santoso & Sriyana, 2020).…”
Section: People's Welfarementioning
confidence: 99%
“…Peri-urban and adjacent areas proximate to large (40,000+) urban centres like Port Moresby, Noumea, Honiara, Suva, Port Vila, Nandi, Lae, Apia and Dededo, require fresh food, resulting in strong links between food production activities and income creation [34]. Urban Honiara (Solomon Islands) has limited employment options, leading to re-selling of produce being the only source of income for more than 80% of roadside vendors [37]. As not everyone has access to the large and usually crowded Honiara Central Market (HCM), roadside produce resellers/ vendors play an important role in the dispersal of fresh produce through Honiara and its environs [33].…”
Section: Plos Sustainability and Transformationmentioning
confidence: 99%
“…Research on small holder agricultural production that includes gendered relations in its analysis has mostly been undertaken in PNG [49,55,56] Solomon Islands [33,37,43,44,81], and to a limited degree in Samoa [60]. There are four common findings across these Pacific Islands states.…”
Section: Gender and Agricultural Production In The Pacificmentioning
confidence: 99%
“…Segregation is recognized as a major barrier in creating an inclusive city and a potential threat to urban economic development, people's wellbeing and social stability. Economic regeneration plays a vital role in realizing urban inclusiveness and is often seen as an effective way to promote the urban economies development and prosperity (Keen and Ride 2019). For example, understanding legal street trading can be seen as a central element in the process of economic regeneration to embrace the involvement of excluded groups (Affleck and Mellor 2006;Agyemang and Morrison 2018).…”
Section: Cluster Analysis Of High-frequency Abstractmentioning
confidence: 99%